2007
DOI: 10.1007/bf03160920
|View full text |Cite
|
Sign up to set email alerts
|

Insulin & C-peptide levels in sulfonylurea-induced hypoglycemia: A systematic review

Abstract: Objectives: We will describe insulin and C-peptide levels observed in sulfonylurea-induced hypoglycemia and determine whether these levels differed if obtained before or after hypoglycemic therapy.Methods: We performed a systematic review of the English literature to identify Medline articles containing "sets" (glucose Ͻ 60 mg/dL with insulin and C-peptide levels). These "sets" were categorized as being obtained BEFORE, AFTER, or UNKNOWN with respect to hypoglycemic therapy.Results: 22 articles, 76 patients, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
(40 reference statements)
0
6
0
Order By: Relevance
“…When endogenous insulin is released from the pancreas, equimolar amounts of the C-peptide are released simultaneously, and the C-peptide is metabolized and cleared more slowly than insulin, so the C-peptide can be used to assess the level of endogenous insulin secretion [ 55 , 56 , 57 ]. In the normal body, the ratio of insulin to C-peptide (I:C) is less than 1 [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When endogenous insulin is released from the pancreas, equimolar amounts of the C-peptide are released simultaneously, and the C-peptide is metabolized and cleared more slowly than insulin, so the C-peptide can be used to assess the level of endogenous insulin secretion [ 55 , 56 , 57 ]. In the normal body, the ratio of insulin to C-peptide (I:C) is less than 1 [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…When endogenous insulin is released from the pancreas, equimolar amounts of the C-peptide are released simultaneously, and the C-peptide is metabolized and cleared more slowly than insulin, so the C-peptide can be used to assess the level of endogenous insulin secretion [ 55 , 56 , 57 ]. In the normal body, the ratio of insulin to C-peptide (I:C) is less than 1 [ 55 ]. When hyperinsulinemia occurs, such as pancreatic β-cell tumors and the rare insulin autoimmune syndrome, the insulin level and C-peptide level increase simultaneously, and the ratio of insulin to C-peptide (I:C) is still less than one [ 55 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quadrani et al reported on 93 children (mean age, 3.5 (from 1 to 16) years) who were each given an overdose of SU by a parent suffering from Münchausen syndrome [6]. The remaining 3 reports did not give detailed information on the suicide attempts, but included patients who had self-destructive habits, psychiatric disorders (including Münchausen syndrome), or caregivers with Münchausen syndrome and were given an overdose of SU intentionally [7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…[5] Naturally, during the current pandemic, it would be tenable that they should be totally avoided due to the high risk of development of hypoglycemia. [7] The use of sodiumglucose-co-transporter 2 inhibitors (such as canagliflozin, dapagliflozin, and empagliflozin) during Ramadan is controversial, nonetheless they should be avoided due to high risk of development of dehydration, diabetic ketoacidosis, and consequent kidney damages in the context of Covid-19. [1,8,9] As patients with diabetes (particularly the elderly with type 2 diabetes) simultaneously consume anti-hypertensive and lipid lowering medications, dose and timing of these drug may also need to be modified in the context of Covid-19 pandemic.…”
Section: Management Of Patients With Type 2 Diabetesmentioning
confidence: 99%